Dinamika Cinta Tidak Romantis dalam Drama Doctor Cha - Puka, Emanuella Fionna Laurel; Luthfiarrahman, Annisa; Latifah, Eva (East Asian Review, 2024)
The issue of romance is frequently used in Korean dramas and favored by the public. Not only romantic love, several Korean dramas also present the issue of non-romantic love. One drama that presents the issue of non romantic love is Doctor Cha. The purpose of this study was to describe the components and forms of love between Cha Jeongsuk and Seo Inho in Doctor Cha based on Sternberg’s Triangular Theory of Love. The research method used was descriptive qualitative with Sternberg’s Triangular Theory of Love. Out of Sternberg’s three components of love, the research findings indicated that intimacy and passion components were not found, but the decision/commitment component was found in Cha Jeongsuk and Seo Inho’s relationship. The type of love experienced by the couple is empty love. However, after the decision/commitment component disappears, the type of love in Cha Jeongsuk and Seo Inho’s relationship changes to nonlove.